EVALUASI TERHADAP PEMBINAAN KINERJA GURU - Yayuk Istikomah; Ahmad Manshur (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study aims to evaluate the implementation of teacher performance development and the effectiveness of evaluation activities in improving teacher professionalism and the overall quality of education. Teachers play a crucial role as planners, implementers, and evaluators of the learning process; therefore, enhancing teacher performance is a key factor in achieving educational success. This research employs a library research method by collecting relevant literature from books, academic journals, and online sources related to the evaluation and development of teacher performance. The findings indicate that teacher performance development has generally been implemented through academic supervision, group discussions, and training activities. However, these programs often remain formal and have not fully addressed the real needs of teachers in the field. The principal plays a central role as a supervisor in providing guidance, feedback, and motivation for teachers to continually improve their competence. On the other hand, the evaluation system for teacher performance development in most schools is still suboptimal due to the lack of systematic follow-up and continuity. Therefore, the evaluation of teacher performance development should be carried out in a systematic, planned, and participatory manner involving all relevant stakeholders. An effective evaluation will provide constructive feedback for teachers and help educational institutions design more targeted strategies for performance improvement. Consequently, the evaluation results can contribute to enhancing teacher professionalism and the overall quality of education.